Albumin concentration is a candidate indicator for predicting the risk of calf venous thromboembolism in patients undergoing gynecologic surgery. Issue 1 (7th July 2021) - Xin, Xing; Huang, Hailong; Lu, Weixin; Li, Yunli; Zeng, Fanke; Wang, Shaoshuai; Feng, Ling
Abstract: Objective: To explore the ability of albumin concentration to predict calf venous thromboembolism (cVTE) in gynecologic diseases. Methods: We analyzed data from 761 patients from the gynecology department. We screened the serum albumin concentration as an important indicator for predicting cVTE through logistic analysis. The data were divided into albumin below 35 and 35 g/L or more. Receiver operating characteristics analysis was used to compare the predictive ability of albumin, D‐dimer, and a combination of these parameters as indicators for cVTE risk in different groups and subgroups. Results: In gynecologic diseases, the albumin concentrations were lower in the surgery and malignancy group than in the chemotherapy and benign disease group. Albumin concentration had a predictive ability for cVTE risk. In ovarian cancer patients with albumin concentrations less than 35 g/L, albumin was better than D‐dimer at predicting cVTE (area under the curve [AUC] 0.79, 95% confidence interval [CI] 0.70–0.87, P < 0.001 versus AUC 0.65, 95% CI 0.54–0.77, P = 0.016). Conclusion: The albumin concentration was a candidate indicator for predicting cVTE in surgical patients in the gynecology department, especially in ovarian cancer patients with albumin concentrations less than 35 g/L. A combination of the albumin and D‐dimer parameters may improve the predictive ability for cVTE. Synopsis: Low albumin concentration is a risk factor for calf venous thromboembolism (cVTE) in gynecologic diseases; albumin concentration can be used as an indicator for predicting cVTE.